The importance of intramolecular ion pairing in intermediate filaments. - Letai, A (1995)
Nuclear and cytoskeletal networks of 10-nm intermediate filaments (IFs) are probably ubiquitous in multicellular eukaryotes. They likely play a role in maintaining the mechanical integrity of a cell. With the exception of the nuclear lamins, IF proteins can form IFs in vitro in the absence of cofactors or associated proteins. Below we present data suggesting that the large alpha-helical "rod" domains of IF proteins are stabilized by large numbers (up to 50) of intra-helical ion pairs formed by residues of opposite charge situated four residues apart. These many ion pairs, sometimes involving up to 30% of the residues within a coiled-coil IF segment, can potentially contribute as much as 10-25 kcal/mol (1 kcal = 4.18 kJ) to the stability of a single alpha-helical rod. Such stabilization is likely to play a major role in the chemical and physical stability of IF networks in vitro and in vivo. An investigation of other coiled-coil proteins shows that selection for intrahelical ion pairing is not simply a property intrinsic to coiled-coil proteins. Rather, there is a correlation between the degree to which there is selection for intrahelical ion pairs and the extent to which a coiled-coil protein participates in highly ordered multimolecular interactions--e.g., as in IFs and myosin thick filaments. The propensity of putative ion pairs in some IF proteins--e.g., epidermal keratins--suggests that an underlying structural stability at the level of the monomer may play an important role in the extraordinary stability of dimers and higher ordered structures in cytoplasmic IFs.